Occupational stress in healthcare staff of four level III health institutions of Cali in Colombia - Sarsosa-Prowesk, Kewy; Charria-Ortiz, Víctor Hugo (Universidad y Salud, 2018)
Introduction: Stress is understood as the set of physiological, behavioral, emotional and cognitive responses, which result in the process of adaptation to the demands derived from the working conditions, before which people evaluate that their coping resources are insufficient. Objective: To identify the level of occupational stress in staff with care positions of four level III health institutions in the city of Cali, Colombia. Materials and methods: A descriptive study with transversal design was made. The third version stress assessment questionnaire was applied Ministry of Social Protection. The sample was 595 participants with care charge, which involves the patient's health care in procedures of high complexity such as surgery, hospitalization, emergencies, intensive care. Results: The staff with healthcare charge of the four level III health institutions presents high level of occupational stress, particularly in the physiological, intellectual and labor symptoms. Conclusions: The prevalence of occupational stress in health care personnel can be associated with the characteristics of role, working conditions and the permanent exposure to communicable diseases inherent in the context of healthcare institutions.